Associations Between Motor Vehicle Crashes and Mental Health Problems: Data From the National Survey of Adolescents‐Replication. Issue 1 (22nd January 2015) - Williams, Joah L.; Rheingold, Alyssa A.; Knowlton, Alice W.; Saunders, Benjamin E.; Kilpatrick, Dean G.
<x xml:space="preserve">Abstract</x> Motor vehicle crashes (MVCs) are a leading cause of physical injuries and mortality among children and adolescents in the United States. The purpose of this study was to examine associations between having an MVC and mental health outcomes, including posttraumatic stress disorder (PTSD), depression, and drug and alcohol misuse in a nationally representative sample of adolescents. A sample of 3, 604 adolescents, aged 12–17 years, was assessed as part of the 2005 National Survey of Adolescents‐Replication (NSA‐R) study. Data were weighted according to the 2005 U.S. Census estimates. Within this sample, 10.2% of adolescents reported having at least 1 serious MVC. The prevalence of current PTSD and depression among adolescents having an MVC was 7.4% and 11.2%, respectively. Analyses revealed that an MVC among adolescents aged 15 years and younger was independently associated with depression (OR = 2.17) and alcohol abuse (OR = 2.36) after adjusting for other risk factors, including a history of interpersonal violence. Among adolescents aged 16 years and older, an MVC was associated only with alcohol abuse (OR = 2.08). This study was the first attempt to explore adverse mental health outcomes associated with MVCs beyond traumatic stress symptoms among adolescents in a nationally representative sample.